Empowerment of Wood Carving Art Groups for Digitalization-Based Sustainable Art and Business in Mas Village, Gianyar: Pemberdayaan Kelompok Seni Pahat Kayu untuk Seni dan Bisnis Berkelanjutan Berbasis Digitalisasi di Desa Mas, Gianyar - Ni Made Wahyuni; Ni Luh Putu Mita Miati; Kadek Goldina Puteri Dewi; Dian Pramana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The art of sculpting is a craft as a branch of the creative economy that focuses on the skill of expressing ideas, thoughts, intellectual works on wood media so as to create products with aesthetic, unique, symbolic, interesting, philosophical meaning and marketability. The lack of knowledge and skills related to the management and business of wood carving makes it interesting to carry out comprehensive empowerment in increasing the potential of carving art in Mas Village, Ubud District. The aim of this community service is to overcome partner problems by helping partners and offering solutions according to the service's field of knowledge. The method of implementing service begins with a location survey, observation, questions and answers regarding the business situation and problems faced. Furthermore, offering solutions in the form of socialization, training, implementation, mentoring, evaluation and sustainability. As a result of the dedication and implications of the program that the 10 members of the sculpture group participated in, they were able to develop knowledge, managerial skills, digital marketing and simple technology-based production. These results can be identified from the results of valid participant questionnaires.